Handbook of carcinogen testing - Milman, Harry A.; Weisburger, Elizabeth K. (Noyes Publications, 1994)
In 1961 the National Cancer Institute initiated a program to conduct bioassays of selected compounds to determine whether they might be carcinogens. Although some similarities continue with the program as it was in 1961, there are many more differences. Since 1985 when the first edition of this book appeared, these differences have been substantial enough to merit an updated version.